2019
DOI: 10.1002/jbt.22332
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin ameliorates ANTU‐induced pulmonary edema and pulmonary arterial hypertension via modulation of VEGF and eNOs

Abstract: Alpha-naphthylthiourea (ANTU), a rodenticide induces lung toxicity. Chrysin a flavonoid possesses antioxidant, anti-inflammatory, and antihypertensive potential.The aim of this study was to evaluate the efficacy of chrysin against ANTU-induced pulmonary edema (PE) and pulmonary arterial hypertension (PAH) in laboratory rats.Sprague-Dawley rats were used to induce PE (ANTU, 10 mg/kg, ip) and PAH (ANTU, 5 mg/kg, ip, 4 weeks). Animals were treated with chrysin (10, 20, and 40 mg/kg) and various biochemical, molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…The synthesis dysfunction of vasodilator NO is well considered a major reason of PAH [ 5 , 6 ]. Abnormal expression and dysfunction of the endothelial NO synthase (eNOS) in the human pulmonary arterial endothelial cells (HPAECs) leads to decreased NO content and thus contributes to the development and progression of PAH [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis dysfunction of vasodilator NO is well considered a major reason of PAH [ 5 , 6 ]. Abnormal expression and dysfunction of the endothelial NO synthase (eNOS) in the human pulmonary arterial endothelial cells (HPAECs) leads to decreased NO content and thus contributes to the development and progression of PAH [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, chrysin treatment after HLI massively increased eNOS mRNA and NO levels compared with the HLI group. Previous studies reported that chrysin increases eNOS mRNA and protein expression (Mizar et al, 2015; L. Wang et al, 2019). NO, which is constitutively produced by eNOS, plays a substantial role in vascular biology and in the regulation of angiogenesis (Cooke & Losordo, 2002; Moncada et al, 1991).…”
Section: Discussionmentioning
confidence: 92%
“…By contrast, chrysin treatment after HLI massively increased eNOS mRNA and NO levels compared with the HLI group. Previous studies reported that chrysin increases eNOS mRNA and protein expression (Mizar et al, 2015;L. Wang et al, 2019).…”
Section: Genementioning
confidence: 95%
“…For HIRT, although it is reported that high-intensity exercise can improve cardiac function, some studies have shown that high-intensity exercise will increase the level of oxidative stress, aggravate endothelial dysfunction, stimulate the increase of ET-1 and inhibit the expression of eNOS. Such changes will affect endothelial function ( Novoa et al, 2017 ; Wang et al, 2019 ). At the same time, the correlation analysis also showed that the correlation between VEGF in myocardium and VEGF in blood was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%